2010
DOI: 10.1242/dmm.003210
|View full text |Cite
|
Sign up to set email alerts
|

Rgs16 and Rgs8 in embryonic endocrine pancreas and mouse models of diabetes

Abstract: SUMMARYDiabetes is characterized by the loss, or gradual dysfunction, of insulin-producing pancreatic -cells. Although -cells can replicate in younger adults, the available diabetes therapies do not specifically target -cell regeneration. Novel approaches are needed to discover new therapeutics and to understand the contributions of endocrine progenitors and -cell regeneration during islet expansion. Here, we show that the regulators of G protein signaling Rgs16 and Rgs8 are expressed in pancreatic progeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 74 publications
3
43
0
Order By: Relevance
“…Rgs16 and its tandemly duplicated paralog, Rgs8 (40), may be general regulators of glucose homeostasis because these genes are expressed not only in liver during fasting but also in islet beta cells during postnatal and embryonic development and even in pancreatic progenitor cells at the initiation of pancreas development (41). Importantly, expression in adult pancreas is suppressed until periods of high insulin demand, as in mouse models of type 1 and type 2 diabetes, and during midgestation in pregnant females.…”
Section: Discussionmentioning
confidence: 99%
“…Rgs16 and its tandemly duplicated paralog, Rgs8 (40), may be general regulators of glucose homeostasis because these genes are expressed not only in liver during fasting but also in islet beta cells during postnatal and embryonic development and even in pancreatic progenitor cells at the initiation of pancreas development (41). Importantly, expression in adult pancreas is suppressed until periods of high insulin demand, as in mouse models of type 1 and type 2 diabetes, and during midgestation in pregnant females.…”
Section: Discussionmentioning
confidence: 99%
“…This approach successfully filters out highly expressed genes in contaminating cell types (e.g., SST, GCG from somatostatin, and glucagon cells contaminating the beta cell population), otherwise mistaken as key players in the expression signature of beta cells. In addition to known beta-cell-specific transcripts (INS, IGF2, PDX1) we highlight further targets, some featured already in a microarray analysis of sorted islet cells (Dorrell et al 2011b), e.g., RGS16, negative regulator of G-protein signaling, involved in endocrine pancreas development and re-expressed in adult cells in response to GLP-1 (Villasenor et al 2010); ADCYAP1, pituitary adenylate cyclase activating polypeptide 1, involved in insulin secretion and beta cell regeneration/proliferation (Sakurai et al 2011); HADH, hydroxyacyl-CoA dehydrogenase, negative regulator of insulin secretion (Hardy et al 2007) associated with Alzheimer's (Nicolls et al 2003), which is in turn associated with diabetes. Many other genes however have not been described before in the context of beta cells, including: NPTX2, neuronal pentraxin 2, found in neuronal cells and gliomas but also shown to be frequently downregulated in pancreatic cancers (Zhang et al 2012); TSPAN1, tetraspanin 1, which can associate with alpha6.beta1 integrin and promote FAK phosphorylation (Huang et al 2008) shown by us to be involved in insulin secretion (Rondas et al 2011); GPM6A, neuronal membrane glycoprotein of unknown function but identified as a beta cell marker in sorted mouse islet cells (Dorrell et al 2011a); BMP5, bone morphogenic protein 5, implicated in pancreas and fetal beta cell development ( Jiang et al 2002); and P2RY1, purinergic receptor through which ADP and ATP modulate insulin secretion (Fernandez-Alvarez et al 2001).…”
Section: à7mentioning
confidence: 99%
“…Intestinal epithelial dynamics polarity (Mailleux et al, 2008;Sternlicht, 2006;Tucker, 2007;Villasenor et al, 2010;Walker et al, 2008). To further investigate this, we examined the Golgi marker Gm130 (Golga2 -Mouse Genome Informatics).…”
Section: Research Articlementioning
confidence: 99%
“…These models are supported by ultrastructural studies that link the initiation of epithelial remodeling to the de novo formation of apical surfaces at so-called secondary lumina located deep within stratified epithelial layers (Madara et al, 1981;Mathan et al, 1976;Toyota et al, 1989) and by recent studies in the zebrafish (Bagnat et al, 2007) and mouse (Saotome et al, 2004) intestine that have pinpointed some of the genes required for this process. Dynamic changes in cell polarity and the fusion of a network of secondary lumina in the context of a transient stratified epithelium were recently shown to drive the formation of murine pancreatic acini (Villasenor et al, 2010). However, in a pseudostratified epithelium, in which all cells already have an apical surface facing the lumen, a more likely mechanism driving remodeling would be cell shape change, coupled with expansion of the existing luminal surface.…”
Section: Introductionmentioning
confidence: 99%